The effects of cash and cash plus interventions on livelihoods outcomes: A systematic review and meta-analysis - Hirvonen, Kalle; Leight, Jessica (International Food Policy Research Institute, 2024)
This presentation was used by the speakers at the brown bag titled "The effects of cash and cash plus interventions on livelihoods outcomes in fragile and non-fragile settings: A systematic review and meta-analysis" held last May 21, 2024 at IFPRI. This work is funded by the CGIAR Initiatives on Fragility, Conflict, and Migration (Work Package 5) and National Policies and Strategies (Work Package 3), as part of a joint project between the CGIAR, the World Food Programme (WFP), and the Norwegian Government.